Asuhan Keperawatan pada Ny. C Keluarga Tn. I dengan Gangguan Sistem Pernapasan : Asma di Desa Kalibuntu RT 02 RW 02 Kecamatan Losari Kabupaten Brebes - Royhan Tsalats Alboughry; Tati Karyawati; Siti Fatimah (Lembaga Pengembangan Kinerja Dosen, 2024)
Asthma is a disease of the respiratory system that causes inflammation or narrowing of the airways that can occur repeatedly due to exposure to allergic agents and this condition can cause shortness of breath for sufferers. According to the World Health Organization (WHO), predicts that by 2025 there will be an increase in the asthma population of 400 million and there will be 250 thousand deaths due to this disease. Data from the Kecipir Health Center in 2023 the incidence of asthma in the Kecipir Health Center working area in Kalibuntu Village is 0.67%. who have asthma. The results of the assessment of the patient said shortness of breath since 5 years ago after doing activities. The nursing diagnosis raised is ineffective airway clearance, and knowledge deficit.